Investigating the Effect of Blended Learning Activity in Teaching Reading at Second Grade Senior High School - Humaira Humaira; Asbah Asbah (Muhammadiyah University of Mataram, 2018)
Blended learning has been growing in popularity as it has proved to be an effective approach for accommodating an increasingly diverse student population while adding value to the learning environment through the incorporation of online teaching resources. This study aims to investigate the effects of The use of blended learning techniques in teaching reading at the second-grade students of Man 2 Model Mataram In Academic Year 2017/2018. The purpose of the study is to know the effect of using Blended Learning technique in teaching reading at the second-grade student of Man 2 Model Mataram. The research method was quasi-experimental research with nonequivalent control group design. The population of the research was of the conducted of two classes as the sample; Experimental group (XI IS 2) and control group ( XI IS 1 ). XI IS 2 was taught by using Blended learning technique of reading while XI IS 1 was taught without Blended learning technique of reading. The researcher gave reading the test to gather the data. The formula that used to analyze the data was t-test. It is supposed to know the significant difference between students’ score in the experimental group and control group. Based on the computation of the t-test formula, it was found that the mean score of the experimental group was 14,21 and the mean score of the control group was 8,42 after analyzing the data,